2006
DOI: 10.1103/physrevb.74.235424
|View full text |Cite
|
Sign up to set email alerts
|

Galvinoxyl monolayers on Au(111) studied by STM, EPR, and cyclic voltammetry

Abstract: Galvinoxyl layers on Au͑111͒ have been studied by scanning tunnelling microscopy ͑STM͒, electron paramagnetic resonance ͑EPR͒, and cyclic voltammetry ͑CV͒. We observe two phases: configuration I having a molecular density of 1.57± 0.16ϫ 10 −10 mol/ cm 2 and a rectangular lattice ͑15 Å by 7 Å͒ observed at room temperature and down to 140 K; configuration II with a slightly smaller molecular density of 1.37± 0.14 ϫ 10 −10 mol/ cm 2 and oblique cells ͑22.5 Å by 5.4 Å͒ arranged alternatingly in stacks yielding a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…This is because the early results presented by Michel [20] were not confirmed in the later studies reported by Pong et al [19]. It has been also shown that galvinoxyl (2,6-di-tert-butyl-a-(3,5-di-tert-butyl-4-oxo-2,5-cyclohexadien-1-ylidene)-p-tolyloxy) molecules deposited on the Au(1 1 1) substrate form two different self-assembled structural configurations and retain their paramagnetic properties [21]. The most recent studies showed that the self-assembled monolayer of family of nitronyl nitroxide radicals (NitRs) can be obtained by immersing of the Au(1 1 1) substrate in dichloromethane solution of NitRs.…”
Section: Introductionmentioning
confidence: 87%
“…This is because the early results presented by Michel [20] were not confirmed in the later studies reported by Pong et al [19]. It has been also shown that galvinoxyl (2,6-di-tert-butyl-a-(3,5-di-tert-butyl-4-oxo-2,5-cyclohexadien-1-ylidene)-p-tolyloxy) molecules deposited on the Au(1 1 1) substrate form two different self-assembled structural configurations and retain their paramagnetic properties [21]. The most recent studies showed that the self-assembled monolayer of family of nitronyl nitroxide radicals (NitRs) can be obtained by immersing of the Au(1 1 1) substrate in dichloromethane solution of NitRs.…”
Section: Introductionmentioning
confidence: 87%
“…The study of surface-bound radicals is directed towards the development of organic ferromagnets that show long range magnetic order in the crystalline phase. TEMPO and galvinoxyl are highly stable radicals that persist at room temperature and have been studied using SAMs [190,204206]. A number of excellent reviews cover the area of PCET in greater detail [66,67].…”
Section: Outer-sphere Effects On Electron Transfer Kineticsmentioning
confidence: 99%
“…Galvinoxyl layers on Au(111) have been studied by STM, EPR, and CV [206]. In the STM, two phases are observed with different molecular densities.…”
Section: Outer-sphere Effects On Electron Transfer Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of works reporting the possibility of keeping paramagnetic properties by nitroxides after the deposition on well-defined surfaces. [24][25][26] The first part of EPR studies was devoted to investigations of powdered (TEMPO) 3 O 3 P compound. In Fig.…”
Section: Results and Discussion Epr Investigationsmentioning
confidence: 99%